Site waste management plan in construction industry / Muhammad Syafiq Mokhtar - Mokhtar, Muhammad Syafiq (Faculty of Architecture,Planning and Surveying, 2015)
Waste disposal problem at the construction site to the impact on developing countries. Disposal of this waste not only affect the view at the construction site, but affect the health of workers .The strategic waste management must be implemented to ensure that developers and contractors can manage solid waste on construction sites in a systematic way, while giving an advantage to the environment. Thus, this dissertation true intention is to know about the regulation and implementation of waste management plan. This dissertation also to identify the factor that contributes to the waste management in construction industry and to determine the best method of waste management that applied on that waste management plan. Taking place in Malaysia, the area of case study of this dissertation is in flat area in Negeri Sembilan..